Secure IT Systems 18th Nordic Conference, NordSec 2013, Ilulissat, Greenland, October 18-21, 2013, Proceedings - Riis Nielson, Hanne; Gollmann, Dieter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 18th Nordic Conference on Secure IT Systems, NordSec 2013, held in Ilulissat, Greenland, in October 2013. The 18 revised regular papers together with 3 short papers and one invited talk were carefully reviewed and selected from 35 submissions. The papers are organized in topical sections on formal analysis of security protocols, cyber-physical systems, security policies, information flow, security experiences, Web security, and network security.
Cyber-Physical Systems -- Security Policies -- Information Flow -- Security Experiences -- Cyber-Physical Systems -- Web Security -- Security Policies -- Network Security.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Computer software; Computer Science; Systems and Data Security; Data Encryption; Algorithm Analysis and Problem Complexity